Prognostic Role of Lymphovascular Invasion in Patients with Urothelial Carcinoma of the Upper Urinary Tract - Mellouli, Manel; Charfi, Slim; Smaoui, Walid; Kallel, Rim; Khabir, Abdelmajid; Bouacida, Mehdi; Nabil Mhiri, Mohamed; Sellami Boudawara, Tahya (Urology Journal, 2017)
Purpose: To evaluate the impact of lymphovascular invasion on the prognosis of patients treated for upper urinary tract urothelial carcinomas. Materials and methods: Clinical records of 49 patients treated surgically at our institute for upper urinary tract urothelial carcinomas were reviewed retrospectively. LVI was defined as the presence of cancer cells within an endotheluim-lined space without underlying muscular walls. Actuarial survival curves were analysed by Kaplan-Meier method. Multivariate analysis was performed using Cox’s proportional hazard model. Results: Median follow-up was 32 months. Lymphovascular invasion was present in 26 (53%) patients. Lymphovascular invasion was associated with higher pathological tumor stage (pT) and higher tumor grade. The disease-free and overall survival rates of the patients with lymphovascular invasion were significantly worse than those of the patients without lymphovascular invasion (p < 0.001 and p = 0.027 respectively). Multivariate analysis revealed that lymphovascular invasion as well as tumor grade and pathological tumor stage were significant prognostic factors for disease-free and overall survival. Conclusion: The presence of lymphovascular invasion was a strong predictor of a poor outcome for UTUC. This finding could help identify patients at greater risk for disease recurrence who would benefit from close follow-up and early adjuvant therapy.